Isoprenaline and inducibility of atrioventricular nodal re-entrant tachycardia - Hatzinikolaou, H (1998)
Objectives—To examine the effect of isoprenaline on slow and fast pathway properties and tachycardia initiation. Design—Consecutive patients, prospective study. Setting—Referral centre for cardiology, academic hospital. Patients—24 patients suffering from common type atrioventricular nodal re-entrant tachycardia (AVNRT). Interventions—Programmed electrical stimulation and radiofrequency catheter ablation of the slow pathway. Measurements and main results—AVNRT was induced before and after the administration of isoprenaline in nine patients (group 1), before isoprenaline only in five (group 2), and after isoprenaline only in 10 (group 3). The anterograde effective refractory period of the fast pathway was prolonged significantly during isoprenaline administration in group 1 (405 (31) v 335 (34) ms, p < 0.001) and shortened in group 2 (308 (57) v 324 (52) ms, p = 0.005). There was also significant shortening in group 3 (346 (85) v 395 (76) ms, p < 0.001). Isoprenaline administration did not result in a significant change of the anterograde effective refractory period of the slow pathway in groups 1 and 3, but eliminated slow pathway conduction in group 2. Isoprenaline significantly shortened the minimal and maximal atrial to His bundle conduction interval recording in response to each extrastimulus of the slow pathway (210 (24) v 267 (25) ms, p < 0.001 and 275 (25) v 328 (25) ms, p < 0.001, respectively) in group 1 and significantly prolonged these intervals (331 (34) v 274 (34) ms and 407 (33) v 351 (33) ms, respectively) in group 3. In all groups only minimal changes in the refractory period of the atrium occurred after isoprenaline administration. The effect of isoprenaline was also measured on the ventricular effective refractory period and on the minimal and maximal length of the ventriculoatrial (V(2)-A(2)) interval during ventricular pacing. Isoprenaline did not result in a significant change of the ventricular effective refractory period in groups 1 and 2 nor of the shortest and longest V(2)-A(2) interval. In group 3, however, the ventricular effective refractory period and the shortest and longest V(2)-A(2) interval shortened significantly after isoprenaline administration. Conclusions—In group 1 isoprenaline did not affect inducibility of AVNRT because it prolonged the fast pathway refractory period without affecting slow pathway conduction. In group 2 isoprenaline shortened the fast pathway refractory period and appeared to abolish slow pathway conduction. Consequencely, isoprenaline prevented induction of AVNRT. In group 3 isoprenaline facilitated induction of AVNRT. This effect seemed primarily to be the result of shortening of retrograde refractoriness of the fast pathway with prolongation of slow pathway anterograde conduction and refractory period.   Keywords: atrioventricular re-entrant tachycardia;  isoprenaline